Editorial: Bibliometric Indicators and Their Accurate Use in the Ranking of Colombian Journals - Melba Libia Cárdenas; María Claudia Nieto Cruz (Universidad Nacional de Colombia, 2018)
The Editors briefly discuss the implications of the latest model for the ranking of scientific journals issued by the Colombian research agency, Colciencias.